Copper removal from contaminated soil through electrokinetic process with reactive filter media. (August 2020) - Ghobadi, Romina; Altaee, Ali; Zhou, John L.; McLean, Peter; Yadav, Sudesh
Abstract: Electrokinetic (EK) remediation has been used in the removal of metal ions from contaminated soil. This study focused on integrating the EK technique with different reactive filter media (RFM) of activated carbon (AC) and biochar (BC) for the first time without adding chemicals to facilitate the removal of copper ions from the contaminated kaolinite soil. Tests based on EK, EK coupled with AC (EK-AC), and EK combined with BC (EK-BC) were performed under an electric potential of 10 V, and the overall removal efficiency of copper ions decreased as EK-BC > EK-AC > EK. The results show that 27% of copper in the soil was captured by BC, compared with only 10% by AC. Additional EK-BC test performed under a constant current (20 mA) revealed that the acid front swept across the soil, resulting in 70.6–95.0% copper removal from soil sections 4 to 1 close to the anode region with more copper accumulation in section 5. Similar to the EK-BC test under a fixed voltage, 26% of copper in the soil was captured by BC during EK-BC treatment under a constant current although with a higher energy consumption. Moreover, RFM was regenerated by flushing with an acid solution, achieving 99.3% of copper recovery in BC and 78.4% in AC. Although the permeability of AC-RFM was higher than that of BC-RFM, copper contaminant was more easily leached out from the BC-RFM. The findings demonstrated the feasibility of contaminant entrapment in BC-RFM and recovery by acid leaching, with potential for sustainable soil remediation. Graphical abstract: Image 1 Highlights: Reactive filter media improved electrokinetic removal of Cu in contaminated soil. Both AC and BC were suitable reactive filter media. Overall removal efficiency decreased as EK-BC > EK-AC > EK. A constant electric current in EK-BC improved Cu removal. Reactive filter media was regenerated and reused.